Structure and associated flora of the Mata de Limón mangrove forest Puntarenas, Costa Rica - Guzmán-Sánchez, Yixlen (2022)
Mangrove forests can be negatively affected by different factors, and variations in these factors can cause physiological stress. The objective of this investigation was to describe the state of the vegetation structure and associated flora of the Mata de Limón mangrove forest. In the year 2014, six plots were established and measurements were carried out in each plot to determine the number of trees, heights, diameters at breast height and species of mangrove to calculate indicators of complexity and importance. Six of the seven nuclear species of Costa Rican mangrove forests were found. The general complexity index was 4.97, and Avicennia germinans had the highest importance value, being present in five of the six plots. In addition, 26 species of associated vegetation were identified, distributed in 17 families. Presence of mangrove forests is determined by the natural dynamics of diverse factors in an ecosystem, but human activities can alter its. The mangrove forest of Mata de Limón has been affected by factors such as the construction of train tracks, roads and the Caldera seaport; its vegetative composition is therefore heterogeneous, with the areas farthest from human interaction displaying greater complexity and a higher presence of floral species typically present in mangrove ecosystems.